2014
DOI: 10.5888/pcd11.140142
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and the Prevalence of Diabetes in US Latino Adults, National Health and Nutrition Examination Survey 2007–2010

Abstract: IntroductionUS Latinos are growing at the fastest rate of any racial/ethnic group in the United States and have the highest lifetime risk of diabetes. Acculturation may increase the risk of diabetes among all Latinos, but this hypothesis has not been studied in a nationally representative sample. The objective of this study was to test the hypothesis that acculturation was associated with an increased risk of diabetes in such a sample.MethodsWe conducted a cross-sectional analysis including 3,165 Latino partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 25 publications
(35 reference statements)
1
52
0
2
Order By: Relevance
“…While recent analyses of nationally representative data from 1980 to 2012 suggest a doubling of the incidence and prevalence of diabetes during 1990-2008 and a plateauing between 2008 and 2012, continued increases were found among non-Hispanic Black and Hispanic populations [1]. Hispanics, the largest ethnic minority group in the United States, have been found to have the highest lifetime risk of diabetes and significantly high rates of comorbid depression [2][3][4]. Prevalence estimates indicate that having diabetes is associated with a twofold higher risk of comorbid depression compared to the general population, with rates among Hispanics as high as 33% [5].…”
Section: Introductionmentioning
confidence: 99%
“…While recent analyses of nationally representative data from 1980 to 2012 suggest a doubling of the incidence and prevalence of diabetes during 1990-2008 and a plateauing between 2008 and 2012, continued increases were found among non-Hispanic Black and Hispanic populations [1]. Hispanics, the largest ethnic minority group in the United States, have been found to have the highest lifetime risk of diabetes and significantly high rates of comorbid depression [2][3][4]. Prevalence estimates indicate that having diabetes is associated with a twofold higher risk of comorbid depression compared to the general population, with rates among Hispanics as high as 33% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that for Latino men and women, rates of diabetes increase with longer tenure in the United States; elevations in BMI could not explain these findings. 28,29 Our research suggests that alongside acculturation, 29 one barrier to better health outcomes for Latinos may be poverty and the unaffordability of nutritious food. Additionally, poverty is a recognized social stressor and has been associated with increased levels of psychological distress 30 and may contribute to the development of biological perturbations that increase diabetes risk.…”
Section: Race Sex and Food Insecurity -Strings Et Almentioning
confidence: 87%
“…Asociaciones similares se notaron entre sobrepeso y obesidad durante la adolescencia, y el riesgo de ERC severa durante la mediana edad 7 . Estudios que incluyeron adultos mayores con tiempos de seguimiento más cortos encontraron asociaciones más débiles entre obesidad y el riesgo de ERC severa [8][9][10] , sugiriendo que la asociación entre obesidad y el riesgo de ERC se limita a individuos con síndrome metabólico y/o hipertensión arterial.…”
Section: Discussionunclassified
“…Para 2030, se calcula un total de 1,12 millones de personas con obesidad 6 . En Latinoamérica se estima, según las cifras obtenidas del NHANES III (National Health and Nutrition Examination Survey III), que un 20% de los hombres y un 25% de las mujeres adultas presentaban obesidad en la década de los noventa, incrementándose su prevalencia a mayor edad (60-69 años) [7][8][9] .…”
Section: Introductionunclassified